Analisis Kesan, Tantangan, Hambatan, dan Harapan Pembelajaran Daring di Era Pandemi Covid 19 - Sebastianus Widanarto Prijowuntato; Aurelia Melinda Nisita Wardhani (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This study aims to analize the online learning process in the Covid 19 pandemic era experienced by students. This analysis is seen from the student's perspective of impressions, challenges, obstacles, and hopes during the learning process during the Covid-19 pandemic. The data collection method in this study used a survey by distributing a google form link to students. The number of respondents in this study were 292 students. The data analysis used included reduction of the data obtained, 2) presentation of the data, and 3) drawing conclusions. The results of this study indicate that there are positive and negative impressions during the online learning process. The negative impressions of the online learning process are supported by the challenges and obstacles experienced by students. In addition, this study also provides an overview of student expectations in the online learning process during the Covid 19 pandemic